2012
DOI: 10.7589/0090-3558-48.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Field Immobilization of Feral ‘Judas’ Donkeys (Equus Asinus) by Remote Injection of Medetomidine and Ketamine and Antagonism With Atipamezole

Abstract: ABSTRACT:The Judas technique is a method used for landscape control of feral donkeys (Equus asinus) in northern Australia. Central to the success of any Judas program is the safe, efficient, and humane attachment of the telemetry device. For feral donkeys, this involves the use of field immobilization. We examine the replacement of the current chemical capture agent, succinylcholine, with contemporary immobilization agents to achieve positive animal welfare outcomes. A combination of medetomidine and ketamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…The overall recumbency time produced by this combination was longer than for many similar studies (e.g. Woolnough et al 2012;Boardman et al 2014). …”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The overall recumbency time produced by this combination was longer than for many similar studies (e.g. Woolnough et al 2012;Boardman et al 2014). …”
Section: Discussionmentioning
confidence: 56%
“…The dose of medetomidine used in the current study was higher than the dose used in a previous study on use in Przewalski's horses (0.07-0.10 mg kg -1 ; Matthews et al 1995), and slightly higher than that used to immobilise feral donkeys (0.14 mg kg -1 ; Woolnough et al 2012). Other studies have shown that comparable doses of medetomidine to those used in the current study have been administered to large ungulates previously without lethal side effects (Tyler et al 1990;Haulena et al 2000;Woolnough et al 2012;Boardman et al in press).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations